Establishment of a New PNA-FISH Method for Aspergillus fumigatus Identification: First Insights for Future Use in Pulmonary Samples - Laura Cerqueira; Sara Moura; Carina Almeida; Maria João Vieira; Nuno Filipe Azevedo (Microorganisms, 2020)
Aspergillus fumigatus is the main causative agent of Invasive Aspergillosis. This mold produces conidia that when inhaled by immunocompromized hosts can be deposited in the lungs and germinate, triggering disease. In this paper, the development of a method using peptide nucleic acid-fluorescence in situ hybridization (PNA-FISH) is described. The PNA-FISH probe was tested in several strains and a specificity and sensitivity of 100% was obtained. Detection of A. fumigatussensu stricto was then achieved in artificial sputum medium (ASM) pre-inoculated with 1 × 102 conidia·mL−1–1 × 103 conidia·mL−1, after a germination step of 24 h. The PNA-FISH method was evaluated in 24 clinical samples (10 sputum, 8 bronchoalveolar lavage (BAL), and 6 bronchial lavage (BL)) that were inoculated with 1 × 104 conidia·mL−1 in sputum; 1 × 103 conidia·mL−1 in BL and BAL, for 24 h. Despite a specificity of 100%, the sensitivity was 79%. This relatively low sensitivity can be explained by the fact that hyphae can yield “fungal ball“ clusters, hindering pipetting procedures and subsequent detection, leading to false negative results. Nonetheless, this study showed the potential of the PNA-FISH method for A. fumigatussensu stricto detection since it takes only 1 h 30 m to perform the procedure with a pre-enrichment step of 6 h (pure cultures) and 24 h (clinical samples), and might provide a suitable alternative to the existing methods for studies in pure cultures and in clinical settings.